Discrimination, Substance Use, and Mental Health among Sexual and Gender Minority Adults Accessing Day Shelter Services. (1st June 2022) - Ehlke, Sarah J.; Cohn, Amy M.; Boozary, Laili K.; Alexander, Adam C.; Waring, Joseph J. C.; Businelle, Michael S.; Kendzor, Darla E.
Abstract: Background: Sexual and gender minority (SGM) adults are overrepresented in the population of individuals experiencing homelessness, and high rates of substance use are common in this group. Plausibly, poor mental health and discrimination may contribute to substance use among SGM adults experiencing homelessness. This study described participant characteristics, and the interrelations among sociodemographic variables, substance use, mental health, and discrimination experiences among 87 SGM adults seeking services at a day shelter in Oklahoma City, OK. Discrimination experiences were characterized by race (White vs. non-White), sex (female vs. male), sexual identity (heterosexual vs. sexual minority), and gender identity (gender conforming vs. gender minority). Methods: Participants reported their past 30-day tobacco (cigarette/cigarillos, alternative tobacco products [ATP]), alcohol, and marijuana use, as well as everyday and lifetime major discrimination experiences, substance use problems, depression, anxiety, and post-traumatic stress disorder (PTSD). Independent samples t-tests examined differences in discrimination based on substance use and mental health. Results: Participants had high rates of tobacco and marijuana use, substance use problems, depression, anxiety, and PTSD. Over 80% reported experiencing everyday or lifetime major discrimination. Depression and PTSD were associated with ATP use, and anxiety was associated with alcohol use. All mental health variables were associated with substance use problems and everyday discrimination. Depression was associated with lifetime major discrimination. Conclusions: SGM adults accessing shelter services frequently experienced discrimination and poor mental health, and substance use was common. Future research should examine the causal impact of discrimination on mental health and substance use among SGM adults experiencing homelessness.